Deciphering proteolysis pathways for the error‐prone DNA polymerase in cyanobacteria. (13th January 2020) - Jin, Haojie; Kim, Rick; Bhaya, Devaki
Summary: Protein quality control pathways require AAA+ proteases, such as Clp and Lon. Lon protease maintains UmuD, an important component of the error‐prone DNA repair polymerase (Pol V), at very low levels in E . coli . Most members of the phylum Cyanobacteria lack Lon (including the model cyanobacterium, Synechocystis sp. PCC6803), so maintenance of UmuD at low levels must employ different proteases. We demonstrate that the first 19 residues from the N‐terminus of UmuD (Sug 1‐19 ) fused to a reporter protein are adequate to trigger complete proteolysis and that mutation of a single leucine residue (L6) to aspartic acid inhibits proteolysis. This process appears to follow the N‐end rule and is mediated by ClpA/P protease and the ClpS adaptor. Additionally, mutations of arginine residues in the Sug 1‐19 tag suggest that the ClpX/P pathway also plays a role in proteolysis. We propose that there is a dual degron at the N‐terminus of the UmuD protein in Synechocystis sp. PCC6803, which is distinct from the degron required for degradation of UmuD in E . coli . The use of two proteolysis pathways to tune levels of UmuD might reflect how a photosynthetic organism responds to multiple environmental stressors.